Influence of post treatment temperature on the toxicity of four macrolacton insecticides against Spodoptera littoralis (BoisduVal) (Lepidoptera:Noctuidae) - Abdu-Allah, G. A.M. (Journal of Phytopathology and Disease Management, 2017)
Temperature is a main ecological factor affect the bioinsecticides toxicity on the destructive larval stage of the cotton leafworm (CLW). The effect of post-exposure temperatures from 13 to 39 °C on the toxicities of two spinosyns (spinosad and spinetoram) and two avermectins (abamectin and emamectin benzoate) toward Spodoptera littoralis (BoisduVal) larvae was evaluated using topical and feeding bioassays. Spinosad and spinetoram showed negative temperature coefficient against CLW larvae. The LD50 values of spinosad and spinetoram increased by 70.21 and > 81.63 folds when temperature increased from 13 to 39 °C. These two compounds also showed negative temperature coefficient values (-1.71; - 9.92) in the feeding bioassay. On contrast, in feeding application abamectin and emamectin benzoate showed high positive temperature coefficient (27.79 and 194.50) when temperature increased from 19 to 39◦C. The present results ascertain the effect of temperature on the pesticides toxicity. So, spinosyins should be applied in cold weather, whereas, abamectin and emamectin benzoate performed well in relative high temperature.